Preclinical research of dihydromyricetin for fibrotic diseases - Wang, Xiao-Chun; Mai, Ping; Yuan, Zuo-Hui; Qiu, Zhi-Sheng (Frontiers in Pharmacology, 2025)
Fibrosis is a pathological condition characterized by excessive deposition of extracellular matrix (ECM) components, leading to tissue scarring and progressive organ dysfunction. The effective treatment of fibrotic diseases remains a pressing challenge in medical research. Dihydromyricetin (DHM), a principal bioactive flavonoid derived from Ampelopsis grossedentata, exhibits diverse pharmacological activities, including anti-inflammatory, antioxidant, and autophagy-modulating effects. This comprehensive review systematically analyzes current research to elucidate the molecular mechanisms underlying DHM’s anti-fibrotic effects across various organ systems. Additionally, we assessed the compound’s chemical properties and toxicological profile. This review aims to advance the understanding of DHM’s therapeutic potential for fibrotic diseases, clarify associated molecular mechanisms, and highlight persistent challenges. We also propose new research directions to further decipher the mechanisms of action of this flavonoid, which may facilitate the development of novel therapeutic strategies for fibrotic diseases.